Postfatigue potentiation of the paralyzed soleus muscle: evidence for adaptation with long-term electrical stimulation training - Shields, Richard K. (2006)
Understanding the torque output behavior of paralyzed muscle has important implications for the use of functional neuromuscular electrical stimulation systems. Postfatigue potentiation is an augmentation of peak muscle torque during repetitive activation after a fatigue protocol. The purposes of this study were 1) to quantify postfatigue potentiation in the acutely and chronically paralyzed soleus and 2) to determine the effect of long-term soleus electrical stimulation training on the potentiation characteristics of recently paralyzed soleus muscle. Five subjects with chronic paralysis (>2 yr) demonstrated significant postfatigue potentiation during a repetitive soleus activation protocol that induced low-frequency fatigue. Ten subjects with acute paralysis (<6 mo) demonstrated no torque potentiation in response to repetitive stimulation. Seven of these acute subjects completed 2 yr of home-based isometric soleus electrical stimulation training of one limb (compliance = 83%; 8,300 contractions/wk). With the early implementation of electrically stimulated training, potentiation characteristics of trained soleus muscles were preserved as in the acute postinjury state. In contrast, untrained limbs showed marked postfatigue potentiation at 2 yr after spinal cord injury (SCI). A single acute SCI subject who was followed longitudinally developed potentiation characteristics very similar to the untrained limbs of the training subjects. The results of the present investigation support that postfatigue potentiation is a characteristic of fast-fatigable muscle and can be prevented by timely neuromuscular electrical stimulation training. Potentiation is an important consideration in the design of functional electrical stimulation control systems for people with SCI.